2013
DOI: 10.1063/1.4801924
|View full text |Cite
|
Sign up to set email alerts
|

Size-selective self-assembly of magnetic Mn nanoclusters on Si(111)

Abstract: We show by first-principles calculations two types of magnetic magic Mn clusters on the Si(111)-(7 × 7) surface. The first is a small triangular Mn7 cluster stabilized by the solid-centered Mn-Si3 bonds on the top layer, and the second is a large hexagonal Mn13 cluster favored by the confining potential wells of the faulted half unit cells on the Si(111) surface. These two structural models are distinct from that of the planar group-III clusters on Si(111) and produce simulated scanning tunneling microscopy im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…1(b) (the energy of the most stable site is set to be 0.0 eV for reference). The present results show that the adsorption energies of the Cu atom in the UHUC sites are about 0.1 eV higher than analogous energies in the FHUC, which is similar to the trend for a variety of other metals (such as Pb, Tl, Sn, Ag, Pd, Mn, Sr, and the alkali metals 4,23,[25][26][27] ) on Si(111)-(7 Â 7) as previously reported. In the FHUC, around the R site (see Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…1(b) (the energy of the most stable site is set to be 0.0 eV for reference). The present results show that the adsorption energies of the Cu atom in the UHUC sites are about 0.1 eV higher than analogous energies in the FHUC, which is similar to the trend for a variety of other metals (such as Pb, Tl, Sn, Ag, Pd, Mn, Sr, and the alkali metals 4,23,[25][26][27] ) on Si(111)-(7 Â 7) as previously reported. In the FHUC, around the R site (see Fig.…”
Section: Resultssupporting
confidence: 90%
“…Overall, from this PES, one can see that the Si(111)-(7 Â 7) surface is considerably corrugated with an energy difference of about 1.5 eV between minima (deep blue regions) and maxima (bright red regions), meanwhile, the nearest distances between them are less than 3 Å. The present results show that, for Cu adsorption, the adatom and rest atom sites have neither the local (or global) energy maxima for Mn adsorption reported by Niu et al 23 and Sr investigated by Zhachuk et al, 25 nor the local (or global) energy minimum found for H adsorption studied by Lo et al 28 In the present system, the most unfavorable adsorption position for the Cu atom localizes in the vicinity of the dimer rows (about 1.5 eV higher in energy than H 2 site), the preference of the H 2 site for Cu shows that the adsorbed Cu atoms prefer to saturate the maximum number of dangling bonds around them.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…For example, self-assembled Mn clusters , and nanowires have been found on the Si(111)-(7 × 7) and Si(001)-(2 × 1) surfaces at a low coverage of Mn, respectively. Theoretical investigations indicate that these surface structures have a FM metallic characteristic. , By controlling the coverage of Mn and the temperature of growth, MnSi 1.7 silicide nanowires , and MnSi silicide thin films were formed on the Si(111)-(7 × 7) and Si(001)-(2 × 1) surfaces, which show FM semiconducting and FM metallic properties, respectively. Meanwhile, the magnetic FeSi 2 , nanowires grown on the Si(110) and (111) surfaces have also been reported.…”
Section: Introductionmentioning
confidence: 99%